The Effect of Sukuk Issuance on Price Reaction and Growth of Sharia Capital Market - Akbar Azis; Cepi Pahlevi; Erlina Pakki (Magister Management, Hasanuddin University, 2021)
This study aims to analyze the effect of the value of Sukuk, Sukuk rating, and risk of Sukuk on the growth of the Islamic capital market mediated by Sukuk price during the period of 2014-2019 using value at risk. This study uses secondary data obtained from the Indonesia Stock Exchange and The Indonesian Capital Market Institute. Data were analyzed using the SPSS statistical program with path analysis techniques. The results of this study indicate that the variable value of Sukuk and the rating of Sukuk have a positive and significant effect on the price reaction of Sukuk, while the risk variable of Sukuk shown a negative and significant score. The variable value of Sukuk has a positive and significant effect on the reaction to the growth of the Islamic capital market, while negative and significant results are indicated by the variable rating of Sukuk and the risk variable of Sukuk. The Sukuk price reaction variables have a positive and significant effect on the reaction to the growth of the Islamic capital market. Interestingly, the study found that the Sukuk price reaction variable is unable to mediate the relationship between the value of Sukuk and the growth reaction of the Islamic capital market. This mediation result is also the same for the Sukuk rating and Sukuk risk.